Bicultural, personality, and pedagogical competences in the perspective of BIPA language assistants - Syihabuddin, Syihabuddin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
In 2019, there were 63.022 learners of Indonesian as a foreign language in Victorian schools, Australia. They were facilitated by 263 Indonesian Language for Foreign Speakers (BIPA) local teachers. Due to a shortage of BIPA local teachers, the Department of Education and Training Victoria had recruited language assistants from Indonesia. This study is aimed to describe the required skillsets of BIPA language assistants to support their duties. The data were collected through interviews, an inventory, observations, and stories of eight Indonesian language assistants with one year of experience. The findings reveal that the language assistants need to develop bicultural, personality and pedagogical competences. These competences should become the reference for developing workshop materials for future BIPA language assistants.